Integrated systems biology analysis of acute lymphoblastic leukemia: unveiling molecular signatures and drug repurposing opportunities - TURANLI, BESTE (My University, 2024)
Acute lymphoblastic leukemia (ALL) is a hematological malignancy characterized by aberrant proliferation and accumulation of lymphoid precursor cells within the bone marrow. The tyrosine kinase inhibitor (TKI), imatinib mesylate, has played a significant role in the treatment of Philadelphia chromosome-positive ALL (Ph + ALL). However, the achievement of durable and sustained therapeutic success remains a challenge due to the development of TKI resistance during the clinical course. The primary objective of this investigation is to propose a novel and efficacious treatment approach through drug repositioning, targeting ALL and its Ph + subtype by identifying and addressing differentially expressed genes (DEGs). This study involves a comprehensive analysis of transcriptome datasets pertaining to ALL and Ph + ALL in order to identify DEGs associated with the progression of these diseases to identify possible repurposable drugs that target identified hub proteins. The outcomes of this research have unveiled 698 disease-related DEGs for ALL and 100 for Ph + ALL. Furthermore, a subset of drugs, specifically glipizide for Ph + ALL, and maytansine and isoprenaline for ALL, have been identified as potential candidates for therapeutic intervention. Subsequently, cytotoxicity assessments were performed to confirm the in vitro cytotoxic effects of these selected drugs on both ALL and Ph + ALL cell lines. In conclusion, this study offers a promising avenue for the management of ALL and Ph + ALL through drug repurposed drugs. Further investigations are necessary to elucidate the mechanisms underlying cell death, and clinical trials are recommended to validate the promising results obtained through drug repositioning strategies. Keywords: Acute lymphocytic leukemia, Philadelphia-positive acute lymphoblastic leukemia, Biomarkers, Drug repositioning, Systems biology
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Hematology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEMATOLOGY; Acute lymphocytic leukemia; Biomarkers; Drug repositioning; Philadelphia-positive acute lymphoblastic leukemia; Systems biology; Acute lymphocytic leukemia; Philadelphia-positive acute lymphoblastic leukemia; Biomarkers; Drug repositioning; Systems biology